Про навчання студентів Чернігівського колегіуму медицині у другій половині XVIII cт. - Травкіна, О.І. (Сіверщина в історії України, 2020)
У статті висвітлюються питання навчання медицині студентів з
Чернігівського колегіуму у другій половині XVIII cт., умови, у тому числі
пільги, які при цьому їм надавалися. Оприлюднено два накази Синоду з
Державного архіву Чернігівської області середини XVIII cт. про запрошення на навчання медицині та фармації українських студентів, в яких
прописані засоби заохочення з метою вступу до шпитальних шкіл. Наголошується на тому, що запрошували студентів, найчастіше, з українських колегіумів, оскільки вони добре володіли латиною, яку викладали
у цих освітніх закладах. Їх забезпечували платнею, харчами, прислугою
та оплачували проїзд. Висвітлюється приїзд в Україну за власною ініціативою професора та дивізійного доктора Івана Андрійовича Полетики з метою набору учнів для шпитальних шкіл з українських навчальних
закладів. Розкривається внесок випускників Чернігівського колегіуму у
розвиток медицини у XVIII cт. Доведено, що поряд з Київською академією Чернігівський колегіум постачав значну кількість студентів для
медичних закладів Росії. Показано, що усього серед вихованців Чернігівського колегіуму близько двадцяти відомих медиків ХVІІІ ст. Вони займалися як клінічною практикою, були знаними хірургами, так і науковими дослідженнями. Українські медики були авторами численних
наукових праць, підручників з медицини. Вони заснували анатомічні
кабінети, природничі музеї, боролися з епідеміями. The article deals with the teaching of medicine of the students of Chernihiv
Collegium in the second half of the eighteenth century and the conditions,
including the privileges that were provided to them. Two orders of the Synod of
the State Archives of Chernihiv region in the middle of the eighteenth century
about the invitation of studying medicine and pharmacy of Ukrainian students,
which spelled out the means of encouragement for the purpose of enrollment
in hospital schools were published. It has been shown that acute shortages
were felt in the professional medical staff for the treatment of the wounded and
sick solders, afloat, especially during the numerous and endless wars that had
been constantly waged by Russia. The reasons of studying Latin in medical
institutions are revealed. It is emphasized that students were invited, most
often, from Ukrainian Collegium, because they had a good command of Latin,
which was taught in those educational institutions. They were originally from
the families of priests, Cossacks, townspeople, and Commonwealths. They were
provided with pay, food, servants and paid for travel. Pupils were required to
have a certificate of study and the passport. Arrival to Ukraine is initiated on
the initiative of Professor and Divisional Doctor Ivan Poletyka for the purpose
of recruiting students for hospitals from Ukrainian educational institutions.
It is noted about his visit to Chernihiv Collegium. The problem of training
professional physicians in connection with the plague epidemic in the early
1770s was shown. It is proved that, together with Kyiv Academy, Chernihiv
Collegium provided a large number of students for medical institutions in
Russia. It is shown that among the students of Chernihiv Collegium there
were about twenty well-known physicians of the eighteenth century. The
contribution of the graduates of Chernihiv Collegium of the development of
medicine in the eighteenth century is revealed.